Factors influencing Vietnam youth’s participation in the nighttime economy - Nguyen, Thi Thu Thuy (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This research examines the factors that influence the behavior of young Vietnamese participants in the nighttime economy (NTE). The established factors were based on the results of a questionnaire distributed among 405 young individuals living, learning, and working in Hanoi, Da Nang, and Ho Chi Minh City. The data obtained confirm the predictive power of the theory of planned behavior (TPB) model to describe the NTE participants’ behavior. The study showed that perceived benefits have a direct influence on NTE participation behavior and an indirect influence through attitudes and the intention to participate; risk perception has only a direct effect on NTE participation behavior. One of the most significant factors in shaping behavioral intentions is financial readiness for consumption, which emphasizes the pragmatism and rationalism of NTE participants in spending their own money. In addition to being pragmatic and rational, the NTE participants’ behavior is influenced by cultural opportunities and the development of nightlife facilities.